Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

i saved the best for last :]

I Saved The Best For Last class=

Sagot :

Answer:

a¹⁸b²⁴c⁵⁴

Step-by-step explanation:

(aᵇ)ᶜ = aᵇᶜ = aᵇ×ᶜ

(-aⁿ)ᵒᵈᵈ = -aⁿ

(-aⁿ)ᵉᵛᵉⁿ = aⁿ

aⁿ × aⁿ = aⁿ⁺ⁿ

_________

In this situation, 6 is an even exponent which means that the negative coefficient of this 9th degree monomial will be positive. Now the only step is to multiply the exponents by the exponent outside of the perenthesis which is 6.

so (-a³b⁴c⁹)⁶ = ((-a³)⁶(b⁴)⁶(c⁹)⁶) = ((a³ˣ⁶)(b⁴ˣ⁶)(c⁹ˣ⁶)) = ((a¹⁸)(b²⁴)(c⁵⁴)) = a¹⁸b²⁴c⁵⁴

Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.